The Effect Of Implementing Content-Based Instruction For Young Learners. - Ima Isnaini Taufiqur Rohmah (Jurnal Pendidikan Edutama, 2015)
The integration of language and content instruction has become a new phenomenon in language education field. The aim of this research is to explore the implementation of Content-Based Instruction and the effect of implementing Content-Based Instruction for young learners. This research used a qualitative research method, in order to be able to observe and get detail information on how the students react and interact in any situation. This research was conducted on the fifth grade students. The data were taken through interview, observation, and analyze the documents. The Result of this study indicated that (1) the implementation of Content-Based Instruction in the fifth grade was well implemented, they used English language as instructional language but it does not supported by appropriate teaching documents. (2) Content Based Instruction automatically give a significance effect to the students’ speaking ability: students could answer the teacher’s questions; the use of mother tongue was reduced. It also improving class situation: the atmosphere in the whole class became alive, there were many chances for students to practice their speaking skill; students had great motivation, learning process became easy and fun for the students.Key words: Content-Based Instruction, Young Learners.